Gender in Play on the Shakespearean Stage Boy Heroines and Female Pages - Shapiro, Michael (University of Michigan Press, 1995)
Cross-dressing, sexual identity, and the performance of gender are among the most hotly discussed topics in contemporary cultural studies. A vital addition to the growing body of literature, this book is the most in-depth and historically contextual study to date of Shakespeare's uses of the heroine in male disguise-man-playing-woman-playing-man-in all its theatrical and social complexity. Shapiro's study centers on the five plays in which Shakespeare employed the figure of the "female page": The Two Gentlemen of Verona, The Merchant of Venice, As You Like It, Twelfth Night, and Cymbeline. Combining theater and social history, Shapiro locates Shakespeare's work in relation to controversies over gender roles and cross-dressing in Elizabethan England.